PROFILE OF CHEMICAL TEACHER CANDIDATES' HIGHER ORDER THINKING SKILLS (HOTS) ON IONIC EQUILIBRIUM IN SOLUTION TOPIC - Abdullah, Abdullah; Albeta, Sri Wilda; Ardiansyah, Ardiansyah (Unnes Science Education Journal, 2018)
This research aims to (1) develop valid questions to measure Higher Order Thinking Skills (HOTS) for chemical teacher candidates on ionic equilibrium in solution topic (2) evaluate chemical teacher candidates’ HOTS on ionic equilibrium in solution topic. Research is a development research type formative research that consist of analyzing, designing, evaluating, and revising. All data are analyzed using descriptive technique. Subject in this research are chemical teacher candidates of University of Riau Chemical Education Study Program. The results of this research are: (1) four of valid HOTS open-ended questions on ionic equilibrium in solution topic. (2) value of chemical teacher candidates’ HOTS on ionic equilibrium in solution topic is 33.18 which put in medium category.